Learning Cultural Arts (Theatre) in Class XI IPS 3 SMA Negeri 1 Lintau Buo Utara - Permata Ayunda; Marzam (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
This study aims to determine and describe cultural arts (theater) learning in grade XI Social Studies 3 at SMA Negeri 1 Lintau Buo. The type of research used is qualitative research with a descriptive approach. The research instrument is the researcher himself and is assisted with supporting tools such as stationery and cameras. Data collection techniques include observation, literature study, interview and documentation study. The steps of analyzing data are, data reduction, data presentation, and conclusion. The results showed that the implementation of cultural arts (theater) learning activities in class XI Social Studies 3 SMA Negeri 1 Lintau Buo using the 2013 curriculum was not in accordance with the syllabus and Learning Implementation Plan (RPP) designed by cultural arts (theater) teachers in grade XI IPS 3 at SMA Negeri 1Lintau Buo, thus impacting on the lack of understanding of students about theatrical arts performances in accordance with the techniques and procedures for designing theatrical arts performances. In order to achieve learning objectives and learning outcomes, teachers must pay attention to the syllabus and Learning Implementation Plan (RPP) that has been designed and can be applied to the learning implementation process regarding the performance of theater arts.